The Islamic Epistemological Worldview and Empirical Study of Socioeconomic Integration in the Ummah - Masudul Alam Choudhury (IIUM, 2016)
This research work done during the author's tenure as professorial chair of Islamic finance in the Institute of Islamic Banking and Finance, IIUM is on the topic of a dynamic study of socioeconomic integration of the Islamic world-system called the ummah taken in its conceptual and empirical contexts. There is also a vast amount of policy and strategic recommendations from the policy-theoretic applied work. The study is different from the usual kind of writings that use sheer empirical models and analysis to study the same topic. Such studies have consistently missed the foundation of the epistemological worldview that is known to comprise the totality of the world-system study. Within this domain lies the epistemological investigation that carries the broad worldview of the values and cultural heritages that are known to colour the total study of the world-system. From such a wide span of the epistemological meaning arise a systemic design of the universe and men’s experience in it as the world-system of balance. Such an experience is exemplified for the ummah